From Intention to Action: Factors Shaping Tourist Decisions to Experience Local Food (PUSA Journal of Hospitality and Applied Sciences, 2025)
Background: Culinary tourism enhances travel experiences by allowing tourists to engage with local cultures through food. Understanding the factors influencing tourists’ decisions to sample and purchase local food is crucial for destination marketers. Objective: This study examines the relationships between Tourist Attitude Towards Local Food (TALF), Tourist Subjective Norms (TSN), Tourist Perceived Behavioural Control (TPBC), Tourist Intention to Sample Local Food (TISLF) and Tourist Decision to Purchase Local Food (TDPLF) in Nainital, India. Methodology: The study adopted a quantitative research design and was conducted in Nainital, a popular tourist destination in Uttarakhand, India. A structured questionnaire was used to collect data from 450 domestic tourists using convenience sampling. Data were analysed using Structural Equation Modeling (SEM) and path analysis through PLS-SEM to assess relationships among key variables and test the proposed hypotheses. Results: TALF, TSN and TPBC significantly influence TISLF, which, in turn, positively affects TDPLF. Social influence, perceived control and positive attitudes shape tourists’ food choices, with food sampling playing a key role in purchasing decisions. Conclusion: The study highlights the importance of social influence, accessibility and cultural authenticity in enhancing culinary tourism. Strengthening these aspects can boost Nainital’s appeal as a gastronomic destination.
Keywords: Tourist behaviour; local food; theory of planned behaviour; culinary tourism; food sampling